BPRS SPM Pamekasan's Strategy in Increasing Multipurpose Savings Customers - Supriyadi; M Rizal Kurniawan (Penerbit Hellow Pustaka, 2025)
This study aims to determine and analyze the marketing strategy carried out by BPRS Sarana Prima Mandiri Pamekasan in increasing Multipurpose Savings Customers and what factors are obstacles in carrying out marketing strategies in increasing Multipurpose Savings Customers at BPRS Sarana Prima Mandiri Pamekasan. This study uses a descriptive qualitative research method with data sourced from primary data and secondary data, and data collection techniques used in the form of observation, interviews and documentation. While the data analysis techniques used are data reduction, data presentation and drawing conclusions. The marketing strategies carried out by BPRS Sarana Prima Mandiri Pamekasan in increasing multipurpose savings customers include: door-to-door visits (from door to door), collective visits (groups), brochure distribution, banner installation, through social media and the outreach system. While the obstacles of BPRS Sarana Prima Mandiri Pamekasan in carrying out marketing strategies in increasing Multipurpose Savings customers are in the form of internal factors, namely, lack of facilities and lack of product understanding. While external factors are, lack of public understanding and many competitors.